1994
DOI: 10.3133/ofr94625
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary geologic map of the Farrier Quadrangle, Clark and Lincoln Counties, Nevada

Abstract: Altitude, height (h), and thickness (t) of alluvial units on the map are given in feet and inches in order for reader to directly correlate such figures with the topographic contours reading in feet; in text all measurements are in metric units as is standard except references to topographic contours are listed in feet and meters. (2) Localities described in text are indexed to the borders of the quadrangle and to the railroad site of Farrier, except that an unofficial place name, Farrier narrows, is used in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
(5 reference statements)
1
16
0
Order By: Relevance
“…The contrasting, strongly upward-coarsening capping beds of the upper Muddy Creek Formation have been recognized across the study area and are generally early Pliocene in age (Schmidt, 1994;Williams, 1996;Pederson et al, 2001). In the western study basins, these capping beds reflect a climatedriven change to the strong progradation of piedmont gravel from local mountainsides into the basins .…”
Section: Muddy Creek Formation North Of Lake Meadmentioning
confidence: 99%
See 2 more Smart Citations
“…The contrasting, strongly upward-coarsening capping beds of the upper Muddy Creek Formation have been recognized across the study area and are generally early Pliocene in age (Schmidt, 1994;Williams, 1996;Pederson et al, 2001). In the western study basins, these capping beds reflect a climatedriven change to the strong progradation of piedmont gravel from local mountainsides into the basins .…”
Section: Muddy Creek Formation North Of Lake Meadmentioning
confidence: 99%
“…At the east end of the study transect, part of this capping unit has been identified as Virgin River gravel entering the Mesquite Basin from the Colorado Plateau (Billingsley, 1995;Billingsley and Bohannon, 1995;Williams, 1996). The early Pliocene change from Muddy Creek deposition to incision of the basin fill is marked by the first of a series of inset piedmont gravels and Virgin River gravels in the Mesquite Basin (Schmidt, 1994;Williams, 1996).…”
Section: Muddy Creek Formation North Of Lake Meadmentioning
confidence: 99%
See 1 more Smart Citation
“…Recharge to the Muddy Creek Formation from stream infiltration along Beaver Dam Wash was estimated to be about 11,000 acre-ft in 1993. Recharge from stream infiltration probably occurs in Beaver Dam Wash where alluvial channel-fill deposits are in contact with coarse, post-Muddy Creek Tertiary gravel similar to the regrade gravel of Moapa, which overlies the fine-grained Muddy Creek Formation about 40 mi west of Beaver Dam Wash (Schmidt, 1994). These outcrops of gravel were observed at several locations upstream from Beaver Dam, Arizona, and generally coincide with areas where losses of streamflow were observed during seepage studies.…”
Section: Rechargementioning
confidence: 99%
“…As much as 200 ft of the upper part of the formation is exposed in these quadrangles; it is light reddish-brown gray and white, slope-forming, finegrained, thin-to thick-bedded, calcareous, gypsiferous, siltstone, sandstone, and calcrete (Billingsley, 1995, p. 11). Billingsley (1995) and Billingsley and Bohannon (1995) do not follow Schmidt (1994) in mapping aggradational and regrade gravels of Tertiary age above the formation; they define conglomeratic gravels of ancestral Beaver Dam Wash and the Virgin River in the upper part of the formation, which may correspond to the post-Muddy Creek Formation gravels defined by Schmidt (1994). Kowallis and Everett (1986, p. 70-75) studied gently northwest-dipping exposures of the Muddy Creek Formation just west of Mesquite, Nevada, about 7 mi southwest of the southern end of the Beaver Dam Wash study area.…”
Section: Muddy Creek Formationmentioning
confidence: 99%